Changing Leadership in Changing Times. Issue 1 (2nd January 2021) - Clegg, Stewart; Crevani, Lucia; Uhl-Bien, Mary; By, Rune Todnem
MAD statement: This leading article is setting out to Make a Difference (MAD) through catalysing the further exploration and development of leadership theory and practice by facilitating the reimagining and reframing of challenges and solutions ahead. It does so by integrating the academic concerns of the current literature with the issues raised by recent events marked by the cataclysmic end of the Trump presidency in the United States.